506. Variation in Occupational Activities and Infection Prevention Practices in Healthcare Personnel Based on Exposure to COVID-19 Units. (31st December 2020) - Howard-Anderson, Jessica; Adams, Carly; Sherman, Amy C; Dube, William C; Smith, Teresa C; Espinoza, Daniel; Zhu, Yerun; Collins, Matthew H; Lopman, Ben; Fridkin, Scott
Abstract: Background: Healthcare personnel (HCP) may be at increased risk for COVID-19, but differences in risk by work activities are poorly defined. Centers for Disease Control and Prevention recommends cohorting hospitalized patients with COVID-19 to reduce in-hospital transmission of SARS-CoV-2, but it is unknown if occupational and non-occupational behaviors differ based on exposure to COVID-19 units. Methods: We analyzed a subset of HCP from an ongoing CDC-funded SARS-CoV-2 serosurveillance study. HCP were recruited from four Atlanta hospitals of different sizes and patient populations. All HCP completed a baseline REDCap survey. We used logistic regression to compare occupational activities and infection prevention practices among HCP stratified by exposure to COVID-19 units: low (0% of shifts), medium (1–49% of shifts) or high (≥50% of shifts). Results: Of 211 HCP enrolled (36% emergency department [ED] providers, 35% inpatient RNs, 17% inpatient MDs/APPs, 7% radiology technicians and 6% respiratory therapists [RTs]), the majority (79%) were female and the median age was 35 years. Nearly half of the inpatient MD/APPs (46%) and RNs (47%) and over two-thirds of the RTs (67%) worked primarily in the ICU. Aerosol generating procedures were common among RNs, MD/APPs, and RTs (26–58% performed ≥1), but rare among ED providers (0–13% performed ≥1). Compared to HCP with low exposure to COVID-19 units, those with medium or high exposure spent a similar proportion of shifts directly at the bedside and were about as likely to practice universal masking. Being able to consistently social distance from co-workers was rare (33%); HCP with high exposure to COVID-19 units were less likely to report social distancing in the workplace compared to those with low exposure; however, this was not significantly different (OR 0.6; 95% CI: 0.3, 1.1). Concerns about personal protective equipment in COVID-19 units were similar across levels of exposure (Table 1). Table 1: Occupational activities and infection prevention behaviors of healthcare personnel stratified by level of exposure to COVID-19 units Conclusion: The proportion of time spent in dedicated COVID-19 units did not appear to influence time HCP spend directly at the bedside or infection prevention practices (social distancing and universal masking) in the workplace. Risk for SARS-CoV-2 infection in HCP may depend more on factors acting at the individual level rather than those related to location of work. Disclosures: Jessica Howard-Anderson, MD, Antibacterial Resistance Leadership Group (ARLG ) (Other Financial or Material Support, The ARLG fellowship provides salary support for ID fellowship and mentored research training) Ben Lopman, PhD, MSc, Takeda Pharmaceuticals (Advisor or Review Panel member, Research Grant or Support, Other Financial or Material Support, Personal fees)World Health Organization (Advisor or Review Panel member, Other Financial or Material Support, Personal fees for technical advice and analysis)